Взаємовідносини ЗУНР і Гетьманату Павла Скоропадського: на різновекторних напрямках - Пиріг, Р. (Краєзнавство, 2018)
У статті досліджується нетривалий період взаємовідносин ЗУНР і Української гетьманської держави у листопаді – грудні 1918 р. Висвітлено звернення галицького проводу за військовою допомогою
до П. Скоропадського, з'ясовано спонукальні мотиви її надання та обставини нереалізованості намірів
гетьмана. Проаналізована реакція Ради Міністрів на львівські події, спроби одночасного встановлення
дипломатичних відносин з регентським урядом Польщі та проводом ЗУНР. Показані заходи демократичної громадськості Наддіпрянщини з підтримки галицьких українців. The article investigates the short period of relations between the ZUNR (West Ukrainian People’s Republic)
and the Hetman’s authority in November – December 1918. The different vector of their state – political
aspirations is emphasized. The appeal of the Halitskyi troops to P. Skoropadskyi for military assistance was
revealed, the motives of its provision and the circumstances of the failure to implement Hetman's intentions
were analyzed. The position of the leaders of the Directorate and the Armed Forces on the priorities of the
liberation struggle is determined. The reaction of the Hetman's government to the Lviv events, in particular
the efforts of the pro-Ukrainian group of ministers to send a diplomatic mission to the ZUNR, the allocation
of financial and military technical assistance, as well as the activity of the right part of the Cabinet of Ministers
to establish diplomatic relations with the Polish Regency Council are analyzed. There are also described activities
of the Naddiprianshchyna democratic community in supporting the brothers – Halicians– publication
of appeals to Ukrainians, the formation of military units, fundraising, etc. It was established that P. Skoropadskyi's
proclamation ofa new political course on federating with non-Bolshevik Russia put an end to the hopes
of a part of the Halician politicians for possible military assistance to the hetman, restrained from establishing
diplomatic relations with him and facilitated the development of a united process with the restored UNR
(Ukrainian People’s Republic).